Single-lateral cervical radiograph in pediatric trauma is equivalent to multiple views. Issue 4 (October 2019) - Lindholm, Erika B.; Malik, Archana; Parikh, Darshan; Mamdouhi, Tara; Alper, Lauren; Nanassy, Autumn; Ciullo, Sean; Arthur, L. Grier; Prasad, Rajeev; Herman, Martin; Grewal, Harsh
Abstract : BACKGROUND: Cervical spine injuries (CSI) are rare within the pediatric population. Due to the significant consequences of missed CSI, children are often imaged excessively. In an attempt to decrease imaging of the cervical spine in children, we reviewed abnormal cervical radiographs (XR) to determine if the diagnosis of CSI could be made using a single-lateral cervical radiograph (LAT). Furthermore, we reviewed cervical computed tomography (CT) and magnetic resonance imaging (MRI) to ensure there were no missed CSI. METHODS: Electronic medical records of trauma patients treated at a Level I Pediatric Trauma Center with abnormal XR findings followed by confirmatory CT or MRI between 2012 and 2017 were reviewed. All abnormal imaging on XR was compared with the LAT. In addition, all abnormal CTs and MRIs were reviewed to ensure there were no false negative XR. RESULTS: A total of 3, 735 XR were performed with 26 abnormal interpretations. All bony CSI were visualized on LAT. Confirmatory imaging found 13 (50%) were false positive and 13 (50%) were true positive. Secondary analysis of CT identified 12 injuries with prior XR; 8 of 12 LAT identifying the injury and 4 of 12 false positive on CT. Secondary analysis of MRI identified nine injuries with prior XR; 5 of 9 LAT identifying the injury. The four false-negative reads on MRI were ligamentous injuries. CONCLUSION: Radiographs are commonly performed when evaluating CSI. In our population, initial assessment with a single LAT was equivalent to a multiple view XR. On secondary review, the only false-negative LAT reports were due to ligamentous injuries. This data suggests limiting exposure to LAT would accomplish the goal of reducing imaging without missing bony CSI and when ligamentous injury is suspected MRI should be the confirmatory study rather than CT. LEVEL OF EVIDENCE: Diagnostic Test, level III.